Peranan Manajemen Berbasis Sekolah dalam Meningkatkan Mutu dan Prestasi Belajar Siswa di SDK Ona Nangahure Pada Masa Pandemi Covid-19 - Yohanes Ehe Lawotan (Peneliti.net, 2021)
This study aims to determine the role of School-Based Management (SBM) in improving the quality and learning achievement of Ona Nangahure Catholic Elementary School students during the COVID-19 pandemic, especially in the components of curriculum management and teaching programs. This study used qualitative research methods. The results of the study show that planning in curriculum development is carried out by compiling an educational calendar, annual program, semester program, syllabus and learning plans that are appropriate during the covid-19 pandemic. The implementation of curriculum development at Ona Catholic Elementary School goes according to plans at the school and class level developed by each teacher so that it runs according to the goals that have been set even though there are problems during the implementation process. While the evaluation in the form of coordination meetings is carried out based on the time allocated to weekly, semester and yearly. From the results of the study, it can be concluded that the role of SBM in improving the quality and learning achievement of students at SD Catholic Ona Nangahure in one component, namely curriculum management and teaching programs, has been in accordance with the steps of curriculum development, namely planning, implementation and evaluation